2014
DOI: 10.1179/1351000214y.0000000105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise training on oxidative stress and mitochondrial function in rat heart and gastrocnemius muscle

Abstract: We hypothesize that the part of Vmax devoted to proton leakage was decreased in trained rats, consequently improving ATP synthesis. The data suggest that, after training, there is more efficient use of electrons in respiratory chain energy production, rather than a greater ROS scavenging capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 46 publications
(53 reference statements)
2
27
0
Order By: Relevance
“…Apart from those given in Table 1, the results on male rats were previously published [16]. These data on male rats are given for comparison with female rats.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Apart from those given in Table 1, the results on male rats were previously published [16]. These data on male rats are given for comparison with female rats.…”
Section: Resultsmentioning
confidence: 99%
“…To compare the results of female rats with the male rats studied in Farhat et al [16], the methods used are the same as those in this previous paper.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Farhat et al indicated that 6 weeks of running on treadmill reduces the production of free OH radicals (11). Yoshida et al also observed that 27 sessions of concurrent training (5 days per week) in patients with cardiovascular diseases reduced oxidative stress through increasing antioxidant capacity (7).…”
Section: Discussionmentioning
confidence: 99%